Energy Efficient Sink Relocation Scheme (Ee-Srs) For Enhanced Network Lifetime in Wireless Sensor Networks (International Journal of Engineering and Computer Science, 2017)
Wireless sensor networks are embedded with distributed set of sensor nodes that are cooperatively monitor physical or environmental conditions, and send their information to a “sink” node over multi hop wireless communication links.  The sensor nodes battery energy depletion will significantly affect the network lifetime of a WSN. Most researchers have aimed to design energy-aware routing protocol to minimize the usage of the battery energy to prolong network lifetimes. This paper proposes a sink relocation approach for efficient utilization of sensor’s battery energy called Energy Efficient Sink Relocation Scheme (E-SRS) which considers regulation of transmission coverage range depend on the residual energy of a sensor node.  The EE-SRS proposed in this paper discusses the algorithm to find the optimal place for relocating the sink, and “when and where to relocate the sink”. The EE-SRS algorithm is developed and simulated using network simulator. The performance analysis has also been done in terms of the network lifetime, throughput and packet delay.